2018
DOI: 10.1051/e3sconf/20184702004
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Different Seaweeds as Diets for Developing Abalone (H. squamata) Culture in Nusa Penida Island, Bali

Abstract: ABSTRACT. Nusa Penida island is one of center for seaweed culture in Bali province. Seaweed that cultured is Euchema spinosum and Euchema cottoni spread around coastal. There also found wild seaweed, such as Ulva sp and Gracillaria sp. Abalone (H. squamata) is one of kind Mollusca which high economic value, but abalone cultured is not yet develop in Nusa Penida island, although this island have high potency for developing abalone culture. Abalone culture needs seaweeds as a diet. The abundance of seaweeds as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…and Ulva sp. found in this study are higher than that reported by Prihadi et al (2018) i.e. Gracillaria sp.…”
Section: Growthcontrasting
confidence: 81%
See 3 more Smart Citations
“…and Ulva sp. found in this study are higher than that reported by Prihadi et al (2018) i.e. Gracillaria sp.…”
Section: Growthcontrasting
confidence: 81%
“…is consistent with a previous study on H. iris (Zhanhui et al 2010) which shows high preference for Gracillaria sp. The high consumption of other macroalgae has also been reported by other studies such as E. spinosum (Prihadi et al 2018), U. lactuca (Angel et al 2012;Bansemer et al 2016) and Enteromorpha sp. (Roussel et al 2020).…”
Section: Feed Intakesupporting
confidence: 78%
See 2 more Smart Citations
“…To test whether food consumption is a function of temperature (Experiment 1), we produced agar-pellets containing Ulva lactuca powder (Xi'an XiaoCao Botanical Development Co., Ltd, China). Ulva lactuca is commonly used as food for abalone in hatcheries and is known to be consumed by H. squamata (Giri et al 2016;Heru Prihadi et al 2018;Yusup et al 2020). For the pellets, we mixed 7.2 g of agar powder with 100 mL of distilled water and boiled the mixture for 5 s in a microwave (800 watts).…”
Section: Herbivores and Macroalgal Foodmentioning
confidence: 99%